2018
DOI: 10.3390/genes9040194
|View full text |Cite
|
Sign up to set email alerts
|

A Key Gene, PLIN1, Can Affect Porcine Intramuscular Fat Content Based on Transcriptome Analysis

Abstract: Intramuscular fat (IMF) content is an important indicator for meat quality evaluation. However, the key genes and molecular regulatory mechanisms affecting IMF deposition remain unclear. In the present study, we identified 75 differentially expressed genes (DEGs) between the higher (H) and lower (L) IMF content of pigs using transcriptome analysis, of which 27 were upregulated and 48 were downregulated. Notably, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated that the DEG perilipin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…A previous study conducting expression profiling of porcine adipose tissue suggested CYBB to play a role in fat metabolism and adipogenic differentiation [ 74 ]. Correlation analysis has also revealed Perilipin 1 ( PLIN 1 ; fold change = -1.42) to be positively correlated with IMF, SFA, MUFA and PUFA and this is in keeping with a previous study reporting its higher abundance being associated with increased IMF in porcine muscle [ 75 ]. Moreover, C-X-C motif chemokine ligand 10 ( CXCL10 , fold change = 2.24), which was previously associated to marbling in cattle [ 76 ], was negatively correlated with IMF, SFA and MUFA.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study conducting expression profiling of porcine adipose tissue suggested CYBB to play a role in fat metabolism and adipogenic differentiation [ 74 ]. Correlation analysis has also revealed Perilipin 1 ( PLIN 1 ; fold change = -1.42) to be positively correlated with IMF, SFA, MUFA and PUFA and this is in keeping with a previous study reporting its higher abundance being associated with increased IMF in porcine muscle [ 75 ]. Moreover, C-X-C motif chemokine ligand 10 ( CXCL10 , fold change = 2.24), which was previously associated to marbling in cattle [ 76 ], was negatively correlated with IMF, SFA and MUFA.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of PPARβ/δ is similar to those of PPARα, which promotes energy dissipation, but opposite to those of PPARγ, which promotes energy storage [33]. PLIN1 was found to promote lipid droplet formation by activating the PPARγ signaling pathway [34].…”
Section: Ppar Pathway Regulates Weakened Lipolysis and Enhanced Lipogmentioning
confidence: 94%
“…Native PLIN1 may serve as a barrier, protecting droplet triglycerides from basal lipolysis, whereas phosphorylated PLIN1 could indirectly activate ATGL [36,37]. Previous studies have found that the expression of PLIN1 was higher in muscles with high IMF contents [34,38]. In addition, AFABP, a negative regulator of mitochondrial fatty acid oxidation [39], was also upregulated in the F line.…”
Section: Ppar Pathway Regulates Weakened Lipolysis and Enhanced Lipogmentioning
confidence: 95%
“…Among these DE genes, downregulated in Iberian LBW animals, Perilipin-1 (PLIN1) is a key gene for porcine adipogenesis, and is closely related to the accumulation of intramuscular fat [87]. LBW Iberian fetuses also exhibited downregulation of CIDEC, which has been linked to adipocyte differentiation and metabolic disorders in humans [88], and which downregulates AMPKα and promotes adipogenesis [89].…”
Section: Foxo1 Foxo3 Foxo6 Col11a2 Myod Igf-i Fos) Protein Catamentioning
confidence: 99%